Batch and dynamic biosorption of basic dyes from binary solutions by alkaline-treated cypress cone chips - Fernandez, Maria Emilia (2012)
A simple alkaline pre-treatment of Cupressus sempervirens cone chips was performed to improve their biosorption capacity towards methylene blue and rhodamine B from aqueous solutions, in batch and continuous modes. Biosorption kinetics were determined from single and binary dyes solutions, and properly described by the pseudo-second-order rate model. Experimental single-dye equilibrium isotherms fitted the Langmuir–Freundlich model, with maximum biosorption capacities of 0.68 mmol/g for methylene blue and 0.50 mmol/g for rhodamine B. Single-dye dynamic biosorption showed that breakthrough time for methylene blue biosorption was almost four times longer than for rhodamine B and that the alkaline modification of the chips greatly improved the biosorption performance. Competitive dynamic biosorption demonstrated the preference of the modified cone chips for biosorbing methylene blue, confirmed by the exit concentration overshoots obtained in the breakthrough curves of rhodamine B.